Comparative analysis of antimicrobial activity of leaf extracts from fresh green tea, commercial green tea and black tea on pathogens - S. Archana, Jayanthi Abraham (Journal of Applied Pharmaceutical Science)
Medicinal plants have been a major source of therapeutic agents for alleviation and cure diseases. In the present investigation comparative analysis of antimicrobial activity of green tea Camellia sinensis fresh leaves, commercial green tea leaves and dust tea against enteropathogens and specific fungi were carried out. The antimicrobial activity of the extracts of Camellia sinensis was analyzed by using well diffusion method paper disk diffusion method and minimum inhibitory concentration. Synergistic activity of green tea and commercial antibiotic chlorophenicol was analyzed. The allopathic antibacterial drugs are said to be costlier and have more side effects. Moreover multiple drug resistant strains are on the raise in this era and thus complicating treatment. On the other hand herbal preparations are comparatively cheaper and have lesser side effects. So, herbal preparations can supplement other systems of medicine for the treatment of diseases caused by bacteria and fungi.
Keywords: Antimicrobial activity, enteropathogens, synergistic activity, polyphenols.